Defluorization of water by a modified membranes from natural materials - Dulneva, T.Yu.; Deremeshko, L.A.; Troianskyi, A.О.; Goncharuk, V.V. (Reports of the National Academy of Sciences of Ukraine, 2022)
Conditions for modification of membranes from natural materials — ceramic from clay minerals and lignocellulosic (from wood) hydroxocompounds Al (III) in the form of dynamic membranes (DM) for water defluorization are established. It is shown that the normative values of MPC for F– in drinking water during defluorination of solutions with ceramic and lignocellulosic membranes were achieved at the initial concentration of F– up to 10 mg/dm3, pH 6.5—7.0, operating pressure 1.0 MPa, concentration Al(III) in the modifying solution, respectively, 33.4—65.0 and 42.2—65.6 mg/dm3 and membrane-supporting additive — 11 mg/dm3. Under these conditions, the concentration of Al(III) in the permeate was lower than its MPC in drinking water. As a result, an additional retention layer in the form of DM was formed on the surface of both membranes from Al(III) hydroxоcompounds, which reduced their specific productivity. The high efficiency of defluorization of solutions can be explained by the formation of stable alumina fluoride complexes between F– ions and positively charged Al(OH)3 particles at pH below the isoelectric point. The adsorption of unbound fluoride ions occurred on the surface of a DM formed of Al(OH)3. An important role in improving the efficiency of the water defluorization process was also played by an additional retention layer of Al(OH)3, which was formed on the surface of both membranes. This was due to the adsorption of F– aluminum hydroxide, which was supplied as a membrane-supporting additive. It is also proposed to use these membranes for the joint purification of water from Al(III) and F– ions at initial concentrations F– up to 10 mg/dm3 and Al(III) 30 mg/dm3, pH 6.5—7.0 and an operating pressure of 1.0 MPa. The effectiveness of defluoridation can be explained by the formation of stable alumina-fluoride complexes that are retained by membranes.